Diversity and community structure of dung beetles (Coleoptera: Scarabaeidae) across a habitat disturbance gradient in Lore Lindu National Park, Central Sulawesi - SHAHABUDDIN SHAHABUDDIN (Biodiversitas Journal of Biological Diversity, 2010)
Shahabuddin (2010) Diversity and community structure of dung beetles (Coleoptera: Scarabaeidae) across habitat disturbance gradient in Lore Lindu National Park, Central Sulawesi. Biodiversitas 11: 29-33. Dung beetles are important component of most terrestrial ecosystems and used to assess the effects of habitat disturbance and deforestation. This study aimed at comparing dung beetle assemblages among several habitat types ranging from natural tropical forest and agroforestry systems to open cultivated areas at the margin of Lore Lindu National Park (LLNP), Central Sulawesi (one of Indonesia’s biodiversity hotspots). Therefore, 10 pitfall traps baited with cattle dung were exposed at each habitat type (n = 4 replicate sites per habitat type) to collect the dung beetles. The resultsshowed that species richness of dung beetles declined significantly from natural forest to open area. However cacao agroforestry systems seemed to be capable of maintaining a high portion of dung beetle species inhabiting at forest sites. The closer relationship between dung beetle assemblages recorded at forest and agroforestry sites reflects the high similarity of some measured habitat parameters (e.g. vegetation structure and microclimate) between both habitat types, while species assemblages at open areas differedsignificantly from both other habitat groups. These results indicated that habitat type has importance effect on determining the species richness and community structure of dung beetles at the margin of LLNP.Key words: forest conversion, diversity, habitat selection, dung beetles marker.